Propagação vegetativa de uma espécie endêmica do bioma Pampa. - Siqueira, Joseane; Bruxel, Fernanda; Orlandi, Carla Roberta; Avrella, Eduarda Demari; Fior, Claudimar Sidnei; de Freitas, Elisete Maria (Ciência e Natura, 2022)
The definition of vegetative propagation methodologies is an alternative for the preservation of endangered native species with potential for economic exploitation, as Hesperozygis ringens. Thus, this study aims to verify the possibility of propagating this species through cutting, testing different substrates and types of cuttings, and comparing the propagation through cuttings obtained from atock plants in a greenhouse and directly in the field. Apical and non-apical cuttings, 6.0cm long, obtained from material from the field and greenhouse, were propagated in trays containing carbonized rice husk and a mixture of carbonized rice husk with coconut fiber powder (2:1, v/v) as substrates. Completely randomized blocks were used in a 2x2 factorial design, with four replicates of 10 cuttings. The plantlets production of H. ringens by cutting is feasible, since it presents a high rooting percentage even when propagules are collected in plants of populations in situ. However, when collected from plants in a greenhouse, the root system of plantlets presents a higher quality than that obtained in field, making possible the production and establishment of plantlets in greenhouses.